2007
DOI: 10.1128/jvi.01267-06
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hijacking of Mitochondrial Lysyl-tRNA Synthetase

Abstract: The primer for reverse transcription of the human immunodeficiency virus type 1 (HIV-1) genome is tRNA 3Lys . During assembly of HIV-1 particles, tRNA 3 Lys is taken up from the host cell along with lysyl-tRNA synthetase (LysRS), the tRNA binding protein that specifically aminoacylates the different tRNA Lys isoacceptors. In humans, the cytoplasmic and mitochondrial species of LysRS are encoded by a single gene by means of alternative splicing. Here, we show that polyclonal antibodies directed to the full-leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 31 publications
6
60
1
Order By: Relevance
“…These findings further define the composition of MSC, in which most components were proposed to have a stoichiometry of one per MSC (31,(43)(44)(45). Close inspection of the published work on previously purified MSCs, from various species, further indicates that, in many preparations, LysRS has twice the density expected for two LysRS molecules per MSC (24,31,46,47). Thus, the organization of the in vitro reconstructed complex reported here may reflect the native architectural arrangement of p38 and LysRS in the mammalian MSC.…”
Section: Discussionsupporting
confidence: 60%
“…These findings further define the composition of MSC, in which most components were proposed to have a stoichiometry of one per MSC (31,(43)(44)(45). Close inspection of the published work on previously purified MSCs, from various species, further indicates that, in many preparations, LysRS has twice the density expected for two LysRS molecules per MSC (24,31,46,47). Thus, the organization of the in vitro reconstructed complex reported here may reflect the native architectural arrangement of p38 and LysRS in the mammalian MSC.…”
Section: Discussionsupporting
confidence: 60%
“…One report suggests that the packaged viral LysRS is of host mitochondrial origin (17). However, earlier studies suggested that packaged LysRS does not appear to originate from any of its identified steady-state cellular compartments, which include the cytoplasmic MSC, nuclei, mitochondria, or cell membrane.…”
mentioning
confidence: 99%
“…However, the mitochondrial species of LysRS is the only species recovered in HIV-1 virions. 10 We tried to evaluate the relative strength of association of cLysRS, pmLysRS and its CAT domain with p38, Pol, p6 ⁎ or IN (Fig. 7b) by introducing the lacZ reporter gene into the two-hybrid assay.…”
Section: Do P38 and Pol Compete For Association With Lysrs?mentioning
confidence: 99%
“…9 As a consequence, the cytoplasmic (cLysRS) and premitochondrial (pmLysRS) LysRS, the mitochondrial species produced in the cytoplasm before maturation during mitochondrial transport, share 576 amino acid residues and display a cross immunological response. 10 The pmLysRS and cLysRS species have specific N-terminal polypeptide extensions of 49 and 21 amino acid residues, respectively. When monospecific antibodies directed to these specific sequences were used to identify the LysRS species packaged into the HIV-1 virions, only the mitochondrial enzyme was detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation